P5.077 Nucleic Acid Amplification Test (NAAT) Diagnostics Combined with Delayed Neisseria Gonorrhoeae Cultivation of NAAT Positive Samples Using the ESwab™ System - the Solution For Future Gonococcal Antimicrobial Susceptibility Surveillance?. (13th July 2013) - Wind, C M; Vries, H J C de; Unemo, M; Dam, A P van
Abstract : Background: Antimicrobial resistance (AMR) in Neisseria gonorrhoeae (Ng) is a major public health problem worldwide. Nucleic acid amplification tests (NAATs) have rapidly replaced cultivation for detection of Ng. We have evaluated the ESwab system for NAAT diagnostics combined with delayed Ng cultivation of NAAT positive samples for gonococcal AMR surveillance. Methods: Based on clinical indications, a urethral, cervical or anal swab was collected from patients with purulent discharge. Gold standard for diagnosis was the APTIMA Combo 2 assay (Gen-Probe). In another study, swabs from urine (UR) and urine sediment (US) were collected if Gram-negative diplococci were observed in direct smears. Flocked swabs were stored in ESwab Liquid Amies (Copan) at room temperature (RT) and 4°C and cultured after 1, 24 and 48 hours. Results: From 35 patients with Ng positive NAAT, we obtained 34 (97%) Ng cultures from ESwab samples stored for 1 hour at RT. Storage for 24 hours at 4°C and RT resulted in 32 (91%) cultures. Storage for 48 hours at 4°C yielded 25 (71%), and at RT only 13 (37%, p = 0.007) cultures. Fourteen urine samples resulted in 13 (UR) respectively 14 (US) cultures after storage for 1 hour at RT. Storage for 24 hours at 4°C and RT resulted in 11 and 7 (UR), respectively 12 and 10 (US) cultures. Storage for 48 hours at 4°C and RT gave 3 and 1 (UR), respectively 5 and 2 (US) cultures. Conclusion: Delayed Ng cultivation from the ESwab system was successful after storage at 4°C for 24 hours in 91% and for 48 hours in 71% of cases. The ESwab system for NAAT diagnostics combined with delayed Ng cultivation of positive NAAT samples appears highly effective for future sustainable and essential gonococcal AMR surveillance. This approach is now being validated in routine practise.